The Influence of Flood Disaster Preparedeness Health Education on The Level of Knowledge and Attitudes of Health Care - Amelia, Rizky; Yuniarti, Yuniarti; Martanti, Listyaning Eko; Rahmawati, Agustin (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
Throughout 2021 the City of Semarang has experienced 88 floods in several different locations. In order for the community to become more independent in the health sector, it is necessary to develop active alert villages and sub-districts where one of the components is health cadres and Health Crisis Management. The community empowers itself through the active role of cadres. Communities prevent, mitigate/reduce the threat and risk of disaster impacts, and increase their ability to adapt, reduce risks, save themselves and recover better. The purpose of this study was to describe the knowledge, attitudes and preparedness of health cadres in dealing with floods as part of community empowerment. This study used a quantitative analytic method, with a cross-sectional technique. It was conducted from August to October 2022. The sample of this study was 35 respondents. The results showed that there was a relationship between the knowledge and attitudes of health cadres towards flood disaster preparedness (p = 0.04 and p = 0.027). The results of the study provide an overview of how preparedness must be owned by every family and health cadre in facing the possibility of natural disasters, in this case floods.